PENILAIAN KINERJA KEUANGAN DENGAN METODE ECONOMIC VALUE ADDED - MULATSIH -; ULFA AULIA PRATIWI (STIE Indonesia Malang, 2017)
Assessment of financial performance to approach EVA (Economic Value Added) is an attempt to assess the extent of the company's success in terms of the interests of investors and creditors. EVA is a measure of financial performance and illustrates the absolute number of shareholders who created or scientific dirusak.Penulisan aims to determine the financial performance of the method of EVA (Economic Value Added) at PT. Mayora Indah Tbk during the years 2011-2015 as well as assessing the EVA (Economic Value Added) produced by the company from 2011 - 2015. Based on the analysis over the period 2011-2015 through the calculation of NOPAT, IC, WACC, Capital Charges, it can be concluded that the performance of PT. Mayora Indah Tbk during the last 5 years were able to generate positive EVA, in 2011 to produce EVA Rp 467 498 482 600, in 2012 to produce EVA Rp 673 325 618 548, in 2013 to produce EVA Rp 947 916 477 646, 2014 produce a value of Rp 495 119 839 388 EVA 2015 and EVA generate Rp 1,180,890,390,993 and approaches Economic value Added (EVA) is very suitable to be applied to the PT. Mayora Indah Tbk because it can provide information to parties - parties that require financial information in particular, the management company in the field of finance and shareholders to make a decision in the future.Keyword: Assessment of Financial Performance, Economic Value Added